ANALISIS POLA UNSUR METEOROLOGI DAN KONSENTRASI POLUTAN DI UDARA AMBIEN STUDI KASUS : JAKARTA DAN BANDUNG (ANALYSIS OF PATTERN OF METEOROLOGY VARIABLE AND AMBIENT POLUTANT CONCENTRATION CASE STUDY : BANDUNG AND JAKARTA) - A. Turyanti; I. P. Santikayasa (Agromet, 2006)
Meteorological conditions are the important factors that influence tranformation and tranportation process of the polutant in the atmosphere. The aim of this research is to study correlation between local meteorology condition with ambient polutant concentration. Case study has been done in Jakarta and Bandung. Research method is secondary data analysis by plot meteorology component (radiation, temperature, hummidity and wind velocity) and polutant consentration, to gain fluctuation pattern from both component and than do correlation analysis. Result of the analysis show that the influence of each meteorology component differ to each polutant component and depend on local condition. In Bandung and Jakarta, radiation fluctuation has negative correlation with CO, NO2, Nox and PM10. The most negative correlation in Bandung is wind velocity with CO which has correlation value -0.74, and correlation between humidity and O3 which has value -0.8. While the most positive correlation is correlation between temperature and radiation with O3 which has value 0.7 – 0.8. Humidity has positive correlation with several polutant. In Jakarta, in general, coefisien correlation value both positive and negative correlation less than coefisien correlation in Bandung, except for O3. The influence of amount and kind of emition also contribute to them. The unique matter has been found that meteorology component fluctuation in both Jakarta and Bandung has high correlation positive and negative with O3, up to the value -0.8 to +0.7. The other polutant component has small in both negative and positive cerrelation (±0.5).